Integrated bioinformatics and experimental analysis of CHAF1B as a novel biomarker and immunotherapy target in LUAD - Wei Du; Xiao-Wei Wu; Qing-Feng Li; Bing-Yu Zhang; Jing Wu; Ya-Ping Xu; Xue Yi (Discover Oncology, 2025)
Abstract The prognosis and treatment efficacy of lung adenocarcinoma (LUAD), a disease with a high incidence, remains unsatisfactory. Identifying new biomarkers and therapeutic targets for LUAD is essential. Chromosomal assembly factor 1B (CHAF1B), a p60 component of the CAF-1 complex, is closely linked to tumor incidence and cell proliferation. However, CHAF1B's biological role and molecular mechanism in LUAD remain unclear. Here, CHAF1B expression in LUAD was examined using the GEPIA2 and UALCAN databases. Using The Cancer Genome Atlas (TCGA) LUAD database, we analyzed the diagnostic and prognostic significance of CHAF1B and its association with immune infiltration and immunological checkpoints. Gene ontology (GO) enrichment and single-cell function analyses were employed to investigate CHAF1B's possible biological roles. Drug sensitivity analysis predicted CHAF1B's effect on chemotherapeutic drug sensitivity. We also predicted lncRNAs-miRNA-CHAF1B axis to explore the molecular mechanism of CHAF1B in LUAD. Preliminary in vitro studies using qRT-PCR, CCK8, Transwell, glucose, and lactate metabolism confirmed CHAF1B's expression and role in LUAD. Its expression is associated with drug sensitivity, immunological checkpoints, and immune cell infiltration. We predicted that three miRNAs (miR-29c-3p, miR-145-5p, miR-1247-5p) and three lncRNAs (AL139287.1, NEAT1, SHG1) may be target miRNAs and target lncRNAs that regulate CHAF1B. In vitro tests showed that CHAF1B suppression decreased LUAD's migration, invasion, proliferation, and glycolysis. Overall, CHAF1B may be an innovative biomarker and therapeutic target for LUAD.